Tawarruq as an alternative to Ar-Rahnu structure / Mohd Shafiz Saharan ... [et al.] - Saharan, Mohd Shafiz; Jamaludin, Mohd Fazil; Adzahar, Khairul Azfar; Wagiran, Norwahida (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
In Malaysia, pawnbroking was introduced by Chinese Hakka from China in the 15th century during the Sultanate of Malacca while trading in Malacca (Mohamad Shukri et al. 2006, Abdul Razak 2011, KPKT 2020). The business starts to grow well, and back in 1871, the Pawnbrokers Ordinance 1871 was introduced by the government. The ordinance was later repealed and replaced by the Pawnbrokers Ordinance 1898 (Wan Abdullah, 1999). To create standardization and harmonization with all the states in Malaysia, the Pawnbrokers Act 1972 and Pawnbrokers Regulation 1972 have taken their place. These acts are under the supervision of the Ministry of Housing and Local Government (KPKT). Currently the latest act governing this industry is Financial Service Act (FSA) 2013. The pawnbroking industry has continuously flourished with ar-rahnu in 1992, which was two decades ago. It was established as an alternative for Muslims other than the conventional pawnbroking. The private and state government have started to introduce ar-rahnu to the society especially to the Muslims even without any specific ruling governing on it. It's now has become a profitable business as more banks and non-bank financial intermediaries start to add ar-rahnu in their business line. The earliest effort was started by Muassasah Gadaian Islam Terengganu by Majlis Agama Islam dan Adat Melayu Terengganu (MAIDAM) (Othman et al, 2013). Besides, Yayasan Pembangunan Ekonomi Islam Malaysia (YaPEIM) also putting their effort to offer arrahnu in Malaysia. In addition, Majlis Agama Islam Kelantan has also established Kedai Ar-Rahnu (KAR), a subsidiary company of Permodalan Kelantan Berhad in the same year.